2016
DOI: 10.1080/19338244.2016.1179168
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between burnout symptoms and Type D personality among health care professionals in Turkey

Abstract: The aim of this study was to investigate the relationship between burnout and Type D personality in health care professionals. The study randomly included 120 health care professionals (73 nurses, 47 doctors). Sociodemographic data form, Maslach Burnout Inventory, and Type D Personality Scale were applied to each participant; 38.3% of the health care professionals (n = 46) had the Type D personality. Emotional exhaustion and depersonalization of health care professionals with Type D personality were higher tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
4
9
0
1
Order By: Relevance
“…These results coincide with those found by Iorga et al [34], who identified neuroticism as the key personal element in developing burnout. The second group, which was also the second most burnt, show a similar pattern to the one established in the literature as Type D personality, identified as risk of developing burnout [47][48][49].…”
Section: Discussionsupporting
confidence: 74%
“…These results coincide with those found by Iorga et al [34], who identified neuroticism as the key personal element in developing burnout. The second group, which was also the second most burnt, show a similar pattern to the one established in the literature as Type D personality, identified as risk of developing burnout [47][48][49].…”
Section: Discussionsupporting
confidence: 74%
“…However, 38.3% of Turkish physicians and nurses [11] and 23–36% of Belgian nurses [22] were reported to have a Type D personality. In terms of prevalence, our study participants (38.6%) are on the higher side when compared to the general population, and are similar to medical personnel.…”
Section: Discussionmentioning
confidence: 99%
“…The Type D personality consists of negative affectivity and social isolation, and is characterized by a depressive, anxious, and inappropriately worrying personality [9]. The proportion of Type D personality among clinical nurses is higher than that of general population, reaching at 36–38%, and nurses with Type D personality experience more compassion fatigue, burnout, and job stress than those with non-Type D personality [10, 11]. Previous studies have observed that Type D personality was positively correlated with PTSD in a group of violence victims [12] and firefighters [13].…”
Section: Introductionmentioning
confidence: 99%
“…Work ability refers to a worker's own assessment of his or her actual professional capacity 8,29,30 whereas psychological distress refers to a continual feeling of anxiety, exhaustion, stress and/ or depression. 9,24,31,32 Sleeping problems refer to insomnia termed as "disorders of initiating and maintaining sleep" 9,[33][34][35] whereas suicidal ideation refers to having thought or planning to commit suicide during or after long continuum of personal distress. 8,9,36 Observed decreases in work-related well-being in physicians is as a key concern worldwide, not only for physicians' personal lives and career paths, but for patient care and health systems as a whole.…”
Section: Introductionmentioning
confidence: 99%
“…8,9,36 Observed decreases in work-related well-being in physicians is as a key concern worldwide, not only for physicians' personal lives and career paths, but for patient care and health systems as a whole. 8,9 From 30% to 40% 9,28 and even up to 75% 37 of physicians globally suffer from reduced workrelated well-being indicated as psychological distress, 9,24,31,32 sleeping problems, 9,35 diminished work ability 8 and suicidal ideations. 8,9,36 Physicians' suicide rates are estimated to be six times higher compared with the general population.…”
Section: Introductionmentioning
confidence: 99%